Voltammetric and electrodeposition study for the recovery of antimony from effluents generated in the copper electrorefining process. Issue 1 (February 2023) - Hernández-Pérez, L.; Carrillo-Abad, J.; Ortega, E.M.; Pérez-Herranz, V.; Montañés, M.T.; Martí-Calatayud, M.C.
Abstract: Antimony is a metalloid with limited availability as a primary resource, but it is commonly found as an impurity in effluents generated in the copper metallurgy. Thus, the development of clean and selective processes to recover antimony from these wastewaters would improve the sustainability of the copper production. In this work, an emulated effluent of the copper electrorefining industry that contains antimony and hydrochloric acid was characterized by means of voltammetric and electrodeposition tests using two different cell configurations: a static cell, and a dynamic cell with a rotating disk electrode (RDE). Voltammograms were obtained at varying hydrochloric acid and antimony concentrations, inversion potentials, scan rates and RDE rotation rates. Two main conclusions were drawn: (a) the deposition of antimony is a mass transfer-controlled process; and (b) an increase in hydrochloric acid concentration improves the deposition of antimony. The diffusion coefficient of antimony species was obtained applying the Randles-Ševčík and the Levich equations; both of them providing very similar values (5.29 ± 0.20 · 10 −6 cm 2 s −1 ). The effective electrodeposition of antimony from highly concentrated hydrochloric acid solutions was demonstrated. The surface examination of the electrodes revealed that compact and adherent deposits of antimony could be obtained under operating conditions that minimize the hydrogen evolution reaction in both potentiostatic and galvanostatic modes. Intensified convective regimes by using the RDE improve the supply of dissolved antimony towards the electrode surface, thus leading to a notorious increase in current density and, consequently, in the rate of antimony deposition. Graphical Abstract: ga1 Highlights: An emulated effluent of copper electrorefining was characterized electrochemically. Sb was recovered despite the high hydrochloric acid concentration. HER competes against the electrodeposition of Sb. Higher hydrochloric acid concentration improves Sb electrodeposition. The least cathodic conditions provided the most compact deposits.